1999
DOI: 10.1038/sj.bmt.1701731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autologous peripheral blood stem cell dosing by ideal vs actual body weight

Abstract: Summary:In this retrospective study, we evaluated the predictability of PBSC dose for hematopoietic engraftment comparing that calculated by ideal body weight (IBW) vs another calculated by actual body weight (ABW) for each patient. Sixty-three consecutive patients treated similarly using one transplant protocol were analyzed. While all patients had data available on CFU-GM and nucleated cells (NC), data on CD34 + enumeration was present only in 34 patients. We found that 49% of the patients were greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…There is evidence that IBW is a better predictor than ABW of cell dose adequacy as measured by recovery of neutrophils after autologous 16,17 as well as allogeneic 18 HSCT. However, there are no data on whether cell dose based on IBW or ABW is a better predictor of TRM and survival -more relevant outcomes than hematologic recovery -after allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that IBW is a better predictor than ABW of cell dose adequacy as measured by recovery of neutrophils after autologous 16,17 as well as allogeneic 18 HSCT. However, there are no data on whether cell dose based on IBW or ABW is a better predictor of TRM and survival -more relevant outcomes than hematologic recovery -after allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have demonstrated that the CD34 þ cell dose based on ideal body weight (IBW) is a better predictor of engraftment. 22,23 Reanalysis of our data using IBW reclassified 17 patients as G-CSF Success, but their PFS and OS remained significantly inferior to those categorized as G-CSF Success by actual body weight (not shown). Consequently, when using mobilization as a predictor of HSCT outcome, classification using actual body weight minimizes false positive mobilization success.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are data suggesting that ideal body weight (IBW) may be a better basis for calculating cell dose, [1][2][3][4][5][6][7] and this is our standard practice. Cell dose based on IBW correlates better with engraftment after autologous 1,3,6 and allogeneic 4,7 HSCT. Cell dose based on IBW also correlates better with more clinically meaningful measures of outcome after allogeneic HSCT such as the risk of GVHD, TRM and disease-free survival.…”
Section: Introductionmentioning
confidence: 99%